Schistosomiasis control in Brazil - Naftale Katz (Memórias do Instituto Oswaldo Cruz., 1998)
In 1975 the Special Programme for Schistosomiasis Control was introduced in Brazil with the objective of controlling this parasitic disease in six northeastern states. The methodology applied varied largely from state to state, but was based mainly on chemotherapy, This Programme was modified about ten years after it beginning with the main goals including control of morbidity and the blockage of establishment of new foci in non-endemic areas. In two states, Bahia and Minas Gerais, the schistosomiasis control programme started in 1979 and 1983, respectively. The recently made evaluation of those two programmes is the main focus of this paper. It must also be pointed out, that the great majority of the studies performed by different researchers in Brazil, at different endemic areas, consistently found significant decrease on prevalence and incidence, when control measures are repeatedly used for several years. Significant decrease of hepatosplenic forms in the studied areas is well documented in Brazil. After more than 20 years of schistosomiasis control programmes in our country, chemotherapy has shown to be a very important tool for the control of morbidity and to decrease prevalence and incidence in endemic areas. Nevertheless, in medium and long terms, sanitation, water supply, sewage draining and health education seem to be the real tools when the aim is persistent and definitive schistosomiasis control.